One size does not fit all: universal cuff overestimates oscillometric blood pressure in persons with large arm circumference - Katrine Bovien Gørlitz; Esben Laugesen; Christian Trolle; Louise Jung Nørgård; Siv Lajlev; Michele Colombo; Mette Bohl; Klavs Würgler Hansen (Blood Pressure)
Objective Some brachial cuffs for oscillometric blood pressure (BP) measurement are claimed to cover a wide range of upper-arm circumferences; however, their validation is rarely conducted. Our aim was to compare oscillometric BP measurements obtained with a universal cuff with those obtained with an appropriately sized cuff.Methods We utilised the Microlife B6 Connect monitor, conducting oscillometric BP measurements in a random sequence with both a universal cuff (recommended for arm circumferences from 22 to 42 cm) and an appropriately sized cuff (medium for circumference 22–32 cm and large for 32–42 cm). We included 91 individuals with an arm circumference of 22–32 cm and 64 individuals with an arm circumference of 32–42 cm.Results For arm circumferences > 32 cm, systolic and diastolic BP measured with the universal cuff was higher than that measured with the large cuff (systolic 6.4 mmHg, 95% confidence interval [CI]). 3.9–8.8, diastolic 2.4 mmHg, 95%CI, 1.2–3.7, p < 0.001 for both). Overestimation of BP with the universal cuff was statistically significant after correcting for the sequence of measurements. No statistical difference was found between the universal cuff and medium cuff for circumferences in the 22–32 cm range. The bladder size in the universal cuff matched the dimensions of the medium-sized cuff; however, the cuff was larger.Conclusion Overestimation of BP measured with a universal cuff in persons with large arm circumferences is clinically important. It poses the risk of unnecessary initiation or intensification of antihypertensive medication in persons using the universal cuff.